THE RELEVANCE OF ORGANIZATION CAPITAL FOR MARKET CAPITAL RETURNS: AN EXTENDED STUDY - Bleoca Lavinia (European Scientific Journal, ESJ, 2014)
This paper extends the existing findings on the theory of “organization capital” proposed by Lev at al. (2009) through a reproduction analysis on newer data, with a different estimation method. A new empirical perspective is proposed, where the intrinsic relationship of the different profitability measures is analyzed in order to offer a survey over the average firm’s capacity of generating excess returns in relation to the closest neighbor, based on its uniqueness. Nevertheless, the analysis seeks to define how profitable unique skills and knowledge are in comparison to the companion portfolio’s, which characteristics are pervasive and how the time-lags of return on investments in knowledge vary between the individual and aggregate levels.